РЕЛІГІЙНИЙ ДИСКУРС ЯК ОБ’ЄКТ МОВОЗНАВЧОГО ДОСЛІДЖЕННЯ ПЕРЕКЛАДІВ МАКСИМА ГРЕКА - Кравцова О. А. (World Science, 2019)
The study was aimed to determine the religion discourse as one which is of great importance in comparative linguistics and theory of translation. It touches both history and theory of translation (grammar theory of translation, in particular) based on such a contradictory personality as Maximus the Greek who left a huge heritage of translated religious texts with his own argumentations of valuable recommendations on how translation of religious texts can impact the understanding of religion in general.